PELATIHAN GURU SLB DALAM KETERAMPILAN SIKAT GIGI PADA ANAK BERKEBUTUHAN KHUSUS MELALUI PRAKTEK PADA BONEKA (Eduscotech, 2022)
Special Needs School Teacher Training on Toothbrushing Skills for Children with Special Needs through Practice with Dolls aims to enhance the capacity of Special Needs School (SLB) teachers in teaching basic self-care skills, particularly toothbrushing, to children with special needs. Many children with special needs, especially those with intellectual and developmental disabilities, experience difficulties in performing personal hygiene activities independently. Therefore, this training introduces an interactive and practical learning approach using dolls as instructional media to facilitate visual and kinesthetic learning.In this training program, participating teachers were guided to use dolls as teaching aids to demonstrate the correct steps of toothbrushing. The training combined theoretical sessions on the importance of oral hygiene with hands-on simulations that allowed teachers to practice and adapt toothbrushing demonstrations for classroom instruction. The use of dolls enabled teachers to present learning materials in a more concrete, engaging, and easily understood manner for children with special needs.The results of this training are expected to improve teachers’ pedagogical skills in delivering self-care instruction and to support the development of children’s independence in maintaining personal hygiene. This activity highlights the effectiveness of practical, visual, and participatory learning strategies in strengthening life skills education for children with special needs in special education settings.